Adaptive Sports Learning in Physical Education: Theory and Practice for Physical Education (PE) Students - I Made Bayu Andika; Perabu Nita; Husni Fahritsani; Sugarwanto Sugarwanto (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objective. The primary goal of this study is to create and evaluate the viability of electronic module instructional resources designed for teaching adaptive sports theory and practical courses. Materials and methods. The study adopted Borg and Gall's research and development theory, which comprises 10 sequential stages. These stages are: (1) research and data collection, (2) planning, (3) initial product development, (4) preliminary field testing involving expert judgment from material experts, media experts, and learning experts, (5) major product revision, (6) large-scale field testing, (7) operational product refinement, (8) operational field testing, (9) final product revision, and (10) dissemination and implementation. However, due to constraints in time and costs, the research only progressed to stage 4, the preliminary field testing. Data was gathered through observations, questionnaires, and interviews. The research employed descriptive qualitative statistics for data analysis. The outcome of the study is an e-module designed for adaptive sports learning theory and practice courses. Results. The feasibility test results for developing e-module teaching materials for adaptive sports learning courses are as follows: media experts found the materials to be very valid and usable, while material experts found them to be valid but needing revisions. The learning experts also found the materials to be valid but needing revisions. The test subjects, consisting of physical education students at PGRI University in Palembang, gave the materials a 62% score, categorizing them as "Decent/Attractive/Good”. Conclusion. The e-modules created for courses on the theory and practice of adaptive sports learning have produced results that make them highly suitable for use as teaching materials for students.